Reward Systems and Performance of Sales: A Descriptive Study among the Ghanaian Insurance Industry - Joshua Ohene-Danso (Centre for Behaviour and Wellness Advocacy, 2015)
Ghanaian managers over recent years have taken a steady pattern of organizational policies, aimed specifically at enhancing employees' development and management. Significant among these measures are recognition and rewards management. The system of rewards at selected Ghanaian Insurance Companies within it Southern Sector operations affected the performance of employees in the sales and marketing of products. Descriptive results indicate that, reward strategies are significant in providing an incentive to employees to work. It is recommended that total rewards should be extended to cover job security and other benefits in the form of recognition.